Successful treatment of tumor-induced osteomalacia causing by phosphaturic mesenchymal tumor of the foot - Liu, Shuzhong (Medicine (Baltimore), 2019)
Tumor-induced osteomalacia causing by phosphaturic mesenchymal tumor of the foot is exceedingly rare, thus may bring great challenges to the timely and proper diagnosis and treatment of clinicians. The only definitive management is removal of the phosphaturic mesenchymal tumor completely. The objective of this article is to report 2 unusual cases with tumor-induced osteomalacia causing by phosphaturic mesenchymal tumor of the foot. We describe 2 patients with phosphaturic mesenchymal tumor involving the foot who were successfully treated with tumor resection. On presentation to our institution, the patients both had signs of severe osteomalacia, and the patients’ most outstanding complaints were diffuse bone pain, general weakness, and disabled walking. A 53-year-old female underwent surgical excision of pathogenic tumor on the sole of left foot. A 62-year-old female underwent complete excision of pathogenic tumor of right plantar. The patients showed appropriate destruction of the tumor, adequate pain relief, and the elevated blood phosphorus levels compared with the previous status. Surgical resection is the most effective treatment option for patients with tumor-induced osteomalacia who can undergo appropriate surgical treatment. This represents a safe and reasonable approach to sustainably relieve pain and other symptoms with tumor-induced osteomalacia in the foot.